Marxist’s Ideology and Revolution Analysis of George Orwell’s Novel “Animal Farm” - Safnidar Siahaan (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This research is presented to discuss about the Marxism ideas in George Orwell’s novel entitled “Animal Farm”. George Orwell wrote Animal Farm to reflect his experience, and responding to the important events that took place in Europe in the first half of the twentieth century. In this research, the author will analyze George Orwell's novel entitled “Animal Farm” focusing on the ideology and the revolution through a Marxist perspective. George Orwell is known as one of the most famous British writers and the fame of his work is still worth studying until now.